Potensi Minyak Herbal STIFA Pelita Mas Terhadap Kadar Ureum dan Kreatinin Tikus Kondisi Hiperglikemik: Potency of STIFA Pelita Mas Herbal Oil on Ureum and Creatinine Levels of Rats Hyperglycemic Conditions - Joni Tandi; Dewi Astuti; Magfirah Magfirah; Tien Wahyu Handayani (KOVALEN: Jurnal Riset Kimia, 2022)
Utilization of natural preparations is a treatment carried out by the community with the aim of improving health status naturally. Traditional medicine has become an alternative for the community due to the relatively high cost of modern medicine. One of the diseases with a high financing burden is kidney disease, which is after heart and blood vessel disease. This study aims to determine the potential of traditional medicinal preparations of Herbal Oil STIFA Pelita Mas on the state of urea and creatinine concentrations in experimental animals, this research used white male rats divided into six treatments. Determination of urea and creatinine levels was carried out starting from days 1, 7, 14, 21 to 28, then normality and homogeneity tests were carried out, and parametric statistics were analyzed using the one-way ANOVA test. The results showed that the administration of STIFA Pelita Mas Herbal Oil in Formula 1, 2, and 3 had urea levels of 42.60 mg/dL, 28.64 mg/dL, and 51.46 mg/dL, respectively. The average values ​​of creatinine in Formula 1, 2, and 3 were 0.73 mg/dL, 0.63 mg/dL, and 0.92 mg/dL, respectively. The administration of Formula 2 was effective in reducing the concentration of urea and creatinine. Pelita Mas herbal oil preparation can be used as a medicine to improve kidney structure.